(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
In the context of the treatment of glomerular diseases, treatment of hepatitis B virus, cytomegalovirus and human immunodeficiency virus plays an important role in diagnosis in children with membranoproliferative, membranous and collapsing glomerulopathy. Otherwise, there is no evidence that identifying a viral infection in a child with glomerulopathy should change the treatment of the infection or glomerulonephritis. Therefore, more research on this topic is greatly needed.